Priscilla P. Clark: The Battle of thè Bourgeois. The Novel in France. 1789-1848. Didier, «Essais et critiques», no. 17. 1973. 219 p. Anthony R. Pugh: Balzans Recurring Characters. University of Toronto Press, 1974, 510 p. Tahsin Yucel: Figures et messages dans la Comédie humaine. Mame, 1972. 230 p. Bernard Vannier: L’inscription du corps. Klincksieck, 1972. 197 p. - Lund, Hans Peter (Revue Romane, 1976)
no abstr.